1999
DOI: 10.1046/j.1365-2044.1999.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

ICU admission in patients infected with the human immunodeficiency virus — a multicentre survey

Abstract: We conducted a retrospective study to assess the reasons for admission to the intensive care unit, and subsequent outcome, in patients infected with the human immunodeficiency virus (HIV). Four hospitals in the south of England participated, all with specialist HIV units. Data were collected on 127 patients admitted to ICU on 133 separate occasions between June 1993 and October 1997. The mean age on admission was 38 years (range 23–60 years). Ninety‐four patients (70.7%) were documented HIV‐positive before adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 13 publications
6
28
2
Order By: Relevance
“…The short-term mortality rate of HIV-infected patients in the present study was similar to the rates reported in the pre-HAART era [5,[8][9][10][11][12][13][14][15]. In-ICU mortality did not change between the pre-HAART and HAART era.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The short-term mortality rate of HIV-infected patients in the present study was similar to the rates reported in the pre-HAART era [5,[8][9][10][11][12][13][14][15]. In-ICU mortality did not change between the pre-HAART and HAART era.…”
Section: Discussionsupporting
confidence: 85%
“…The present study provides the first HAART-era data on long-term survival of HIV-infected patients after ICU discharge. Clearly, the median and mean survival times reported here, as well as the cumulative survival after ICU discharge, were far better than in earlier studies [5,7,9,10,13,14]. We found significant improvements in survival times between the pre-HAART and HAART eras.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Until the mid-90 ties, respiratory failure associated predominantly with Pneumocystis pneumonia (PCP) was the main reason for ICU hospitalization of HIV patients associated with high mortality [5,6]. Further studies, connected with the introduction of HAART, have demonstrated improved survival, even amongst PCP patients [7,8]. At present, respiratory failure is still the most common indication for ICU admission [9,10], although PCP as a cause of respiratory failure is substantially less common.…”
Section: Discussionmentioning
confidence: 99%